International airports as agents of resilience. (4th March 2022) - Horton, Robert; Kiker, Gregory A.; Trump, Benjamin D.; Linkov, Igor
Abstract: The Dallas‐Fort Worth International Airport is used as an example of how traditional approaches of hardening isolated components of critical infrastructure against specific threats leaves critical assets exposed to significant,  expensive, and unacceptable levels of cascading failure. Optimizing the entire airport supply chain requires the development of an interdisciplinary approach that incorporates the complexities of the airports' supply chain including numerous dependent, interdependent and independent relationships. Far greater return‐on‐investment will be yielded through resilience‐focused approaches that address the entire life cycle of disruptions including planning, absorption, recovery and adaptation.